El proceso de morir : destino y significación del diagnóstico de muerte inminente (2013)
ABSTARCT: This article presents a reflection derived from the qualitative research called “Meaning of the Diagnosis of Imminent Death for the Patient with Cancer and his/her Family, and its Effects on the Evolution of the Dying Process”, in which a hermeneutical phenomenological approach was used. The reflection is focused on one of the main findings concerning the management and course of the information once it is revealed to the family. Our results show that the diagnosis of imminent death shakes the family structure, generating attitudes such as defensive reactions, a conspiracy of silence, overprotection and excessive compassion. We discuss these reactions and give emphasize to the paradoxes and contradictions implied in the actions that are, supposedly, adopted as mechanisms to protect from suffering to the patient and the family.